The Impact of Physical Activity to Physical Fitness and Nutrional Status of Grade X Surabaya Vocational High School - Galih Prasetyo; Suroto; Dwi Cahyo Kartiko (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The purpose of this research is to improve physical fitness which is one of the goals of physical education in Indonesia while also improving the nutritional status of Surabaya vocational high school students. This research uses the treatment of physical activity 3 times a week in 2 months as a task in physical education to improve physical fitness and nutrional status on the sample of this research. Research design uses quasi experimental design with metode non-randomized control group pretest-posttest design. Research data was obtained as follows: data processing result on experiment group show that physical activity to VO2max got significant score based calculating using SPSS of 0,00 and physical activity to nutrional status got sig. of 0,60. Whereas in the control group, physical actifity got sig. of 0.20 to VO2max and sig. to 0.11 on nutrional status. Based on the above analysis it can be concluded that physical activity has a significant effect on physical fitness but physical activity has no significant effect on nutrional status to Surabaya vocational high school students.